1987
DOI: 10.2136/sssaj1987.03615995005100030035x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Zone Soil Temperature and Early Corn Growth with Three Conservation Tillage Systems

Abstract: Detailed data are needed to quantify the effect of conservation tillage (CT) on corn (Zea mays L.) emergence and early growth in the Northern Corn Belt. Corn was grown using three CT systems: till‐plant (TP), chisel (CH), and no‐till (NT) and conventional moldboard plow (CN) on a Griswold silt loam soil (Typic Argiudoll) during the 1982 to 1984 growing seasons. Soil temperature at the seed depth (5 cm) was measured hourly. Daily means and cumulative growing degree days (GDD) based on seed zone temperatures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 0 publications
6
46
0
1
Order By: Relevance
“…1). Lower corn biomass early in the season with NT compared with MP treatments has also been observed by Phillips (1983) and Al-Darby and Lowery (1987).…”
Section: Effect Of Tillage and Residue Management On Corn Performancesupporting
confidence: 66%
“…1). Lower corn biomass early in the season with NT compared with MP treatments has also been observed by Phillips (1983) and Al-Darby and Lowery (1987).…”
Section: Effect Of Tillage and Residue Management On Corn Performancesupporting
confidence: 66%
“…Soil test P values in the top 15 cm were 46 mg kg −1 for CP−, 90 mg kg −1 for CP+, 35 mg kg −1 for NT−, and 85 mg kg −1 for NT+. Soil test P levels (0–15 cm) were significantly higher in CP possibly due to greater mineralization of organic P compounds due to residue incorporation and higher soil temperatures generally associated with CP vs. high‐residue NT systems (Dalal, 1977; Al‐Darby and Lowery, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…No consistent benefit of increased emergence or grain yield from in‐row subsoil tillage was noted on these sandy soils. When increased plant performance due to tillage has been measured, it is usually a result of warmer soil temperatures (1). In these studies, tillage did not result in increased soil temperature in the furrow at normal seeding depth.…”
Section: Discussionmentioning
confidence: 99%
“…While Alessi and Power (2) demonstrated that seeding depth affects the rate and time of corn emergence, they found temperature has the most control over time to emergence. Soil temperatures are influenced by tillage and impact is greater during the first five weeks after planting increasing plant height, leaf area, and overall dry matter accumulation (1). Gupta et al (8) have demonstrated that shallower planting can decrease the time to emergence in cooler soils.…”
Section: Introductionmentioning
confidence: 99%